Documenting glacial changes between 1910, 1970, 1992 and 2010 in the Turgen Mountains, Mongolian Altai, using repeat photographs, topographic maps, and satellite imagery. Issue 3 (18th February 2013) - Kamp, Ulrich; McManigal, Kevin G; Dashtseren, Avirmed; Walther, Michael
Abstract : The Turgen Mountains lie in northwestern Mongolia, roughly 80 km south of the Russian border. The area was visited in 1910 by a Royal Geographical Society expedition led by Douglas Carruthers. The party undertook an extensive survey of the range and also documented the extent of the glaciers with photographs. One hundred years later, in summer 2010, a US–Mongolian expedition retraced portions of the 1910 expedition. Camera locations were matched to the historical photographs and repeated photographs taken. In addition, the termini of the two main glacial lobes were surveyed by GPS. Analyses of field data, repeated photographs from 1910 and 2010, topographic maps from 1970, and satellite imagery from 1992 and 2010 were used to describe the changes in the glacial system. The results suggest that while the snow and ice volume on the summits appears to be intact, lower elevation glaciers show significant recession and ablation. From 1910 to 2010, West Turgen Glacier receded by c . 600 m and down‐wasted by c . 70 m. This study successively demonstrates the utility of using historic expedition documents to extend the modern record of glacial change.